Demand of One Health Activities by Community-Level Service Providers in Selected Districts of Nepal - Bagal, Kosh Bilash; Adhikari, Ramesh; Acharya, Devaraj; Devkota, Bhimsen; Shrestha, Suresh (Asian Journal of Population Sciences, 2023)
One Health (OH) is a new approach to controlling zoonoses in the veterinary and public health fields in Nepal. This study aims to explore the OH-related knowledge, perception, and practices of service providers like veterinarians, public health, and livestock-related cooperative members in selected districts of Nepal. We randomly selected three municipalities from three districts of Gandaki province in Nepal using by qualitative dominant mixed-method research approach for data collection. The study showed that most of the respondent service providers had a low level of knowledge of the OH approach and conducted their zoonoses control programs vertically in a traditional way. Foot and mouth disease (FMD), brucellosis, Peste des petits ruminants (PPR), rabies, leptospirosis, and bovine tuberculosis (BTB) are livestock-related common zoonoses and dog bites, worm infestation, diarrhoeal diseases showed the common health problems in public health sectors in the study. This prevalence creates a higher zoonoses risk in farming communities of Nepal. Therefore, to control the zoonoses we need to make knowledgeable service providers who are engaged basically in human and animal health care sectors by applying the OH approach. Government should introduce OH-related programs up to the community level and should establish the OH committee at every local level with united all public health, animal health, and water sanitation and hygiene (WASH) related officials in the country.